Cryorolling effect on microstructure and mechanical properties of Fe–25Cr–20Ni austenitic stainless steel. (25th December 2015) - Xiong, Yi; He, Tiantian; Wang, Junbei; Lu, Yan; Chen, Lufei; Ren, Fengzhang; Liu, Yuliang; Volinsky, Alex A.
Abstract: Microstructure and mechanical properties of the Fe–25Cr–20Ni austenitic stainless steel after cryorolling with different reductions were investigated by means of optical, scanning and transmission electron microscopy, X-ray diffraction and mini-tensile testing. High density tangled dislocations and a small amount of deformation twins formed after 30% deformation. After 50% strain, a large amount of deformation twins was generated. Meanwhile, interactions between the twins and dislocations started to happen. As the strain increased to 70%, many deformation twins were produced and the interactions between the twins and dislocations were significantly enhanced. When the cryorolling was 90%, the grain size was refined to the nanometer scale. XRD analysis indicated that the diffraction peaks of the samples became broader with the strain increase. The yield strength and the ultimate strength increased from 305 MPa and 645 MPa (before deformation) to 1502 MPa and 1560 MPa (after 90% deformation), respectively. However, the corresponding elongation decreased from 40.8% to 6.4%. The tensile fracture morphology changed from typical dimple rupture to a mixture of quasi-cleavage and ductile fracture. After 90% deformation, the microhardness was 520 HV, which increased by 100% compared with the original un-deformed sample. Graphical abstract: Highlights: Diffraction peaks of Fe–25Cr–20Ni stainless steel broadened with strain increase. When the cryorolling was 90%, the grain size was refined to the nanometer scale. Hardness and strength increased, but elongation decreased with cryorolling. Fracture morphology changed from ductile to brittle fracture with cryorolling.